Conduit Dynamics in Transitional Rhyolitic Activity Recorded by Tuffisite Vein Textures from the 2008–2009 Chaitén Eruption - Saubin, Elodie; Tuffen, Hugh; Gurioli, Lucia; Owen, Jacqueline; Castro, Jonathan M.; Berlo, Kim; McGowan, Ellen M.; Schipper, C. Ian; Wehbe, Katia (Frontiers in Earth Science, 2016)
The mechanisms of hazardous silicic eruptions are controlled by complex, poorly-understood conduit processes. Observations of recent Chilean rhyolite eruptions have revealed the importance of hybrid activity, involving simultaneous explosive and effusive emissions from a common vent. Such behaviour hinges upon the ability of gas to decouple from magma in the shallow conduit. Tuffisite veins are increasingly suspected to be a key facilitator of outgassing, as they repeatedly provide a transient permeable escape route for volcanic gases. Intersection of foam domains by tuffisite veins appears critical to efficient outgassing. However, knowledge is currently lacking into textural heterogeneities within shallow conduits, their relationship with tuffisite vein propagation, and the implications for fragmentation and degassing processes. Similarly, the magmatic vesiculation response to upper conduit pressure perturbations, such as those related to the slip of dense magma plugs, remains largely undefined. Here we provide a detailed characterization of an exceptionally large tuffisite vein within a rhyolitic obsidian bomb ejected during transitional explosive-effusive activity at Chaitén, Chile in May 2008. Vein textures and chemistry provide a time-integrated record of the invasion of a dense upper conduit plug by deeper fragmented magma. Quantitative textural analysis reveals diverse vesiculation histories of various juvenile clast types. Using vesicle size distributions, bubble number densities, zones of diffusive water depletion, and glass H2O concentrations, we propose a multi-step degassing/fragmentation history, spanning deep degassing to explosive bomb ejection. Rapid decompression events of ~3-4 MPa are associated with fragmentation of foam and dense magma at ~200-350 metres depth in the conduit, permitting vertical gas and pyroclast mobility over hundreds of metres. Permeable pathway occlusion in the dense conduit plug by pyroclast accumulation and sintering preceded ultimate bomb ejection, which then triggered a final bubble nucleation event. Our results highlight how the vesiculation response of magma to decompression events is highly sensitive to the local melt volatile concentration, which is strongly spatially heterogeneous. Repeated opening of pervasive tuffisite vein networks promotes this heterogeneity, allowing juxtaposition of variably volatile-rich magma fragments that are derived from a wide range of depths in the conduit. This process enables efficient but explosive removal of gas from rhyolitic